Analisis Faktor Yang Mempengaruhi Minat Siswa Memilih Kegiatan Ekstrakurikuler Pramuka Dan Tahfidz di SMPN 4 Kecamatan Bukit Barisan Kabupaten 50 Kota - Sestika Susanti; Supriadi Supriadi; Deswalantri Deswalantri; Jasmienti Jasmienti (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2023)
This research is based on problems regarding students who are less interested in participating in extracurricular activities, students in the process of participating in extracurricular activities are less enthusiastic about following directions, and lack the ability to focus. With this, the problem can be formulated from this, namely what are the factors that influence students' interest in choosing extracurricular activities at SMPN 4 Bukit Barisan District. The aim of this research is to reveal the factors that influence students' interest in choosing scout and tahfidz extracurricular activities at SMPN 4, Bukit Barisan District, 50 City District. This type of research uses field research which is descriptive quantitative using factorial analysis. The key informants were class VII students and class VIII students, as well as supervising teachers in extracurricular activities. To collect data, the authors conducted interviews and questionnaires (questionnaire). After the data is collected, it is processed and analyzed. The result of the research is that students' interest in choosing extracurricular activities at SMPN 4 Bukit Barisan District. Factors that influence student interest are intrinsic factors which include ability, temperament, character, physical structure, teachers, facilities, peers, habits. . The results of the analysis obtained are the matrix component values ​​for the ability variable (0.852), temperament variable (0.727), physical structure variable (0.835), teacher variable (0.849), facility variable (0.816), peer variable (0.851), parents (0.821 ), habit variables (0.812). From the results of this research it can be concluded that the variables are willingness, needs, motivation, family support, school environment. So the researcher concludes that the most dominant factor influencing students' interest in choosing extracurricular activities is the factor that has the highest value, namely ability variable (0.852). This shows that most students' interest in choosing extracurricular activities is influenced by the students' own abilities, so teachers should always arouse students' interest in choosing extracurricular activities through developing the factors that influence them in each extracurricular activity, especially the students' abilities.